KANDUNGAN KUERSETIN DAN POLA PROTEOMIK VARIETAS JAMBU B ATU (Psidium guajava L.) TUMBUH LIAR DIKAWASAN CIBINONG, BOGOR - Jusuf, Eddy (Research Center for Biology-Indonesian Institute of Sciences, 2010)
This work was purposed to discover the potencies of some guava Psidium guajava) varieties or cultivars as medicinal and fruit plant, from which the economic value then would be raised. We have collected from about 500 hectares area of our institute including the village surroundings, 35 numbers of morphologically different guavas wild growing consisting of 18 cultivars of red fruit and 17 of white fruit. Methanol extraction of dried leaves giving flavonoids, which by thin layer chromatography Kieselgel 60F2S4, the spots of quercetin of HRf > 50 obtained from all guava varieties. After extraction of each spot and measuring spectrophotometrically, the quercetin content of each plant number was found to be varied in both, among red fruit and white fruit varieties. The highest, >6.0% quercetin content obtained in two numbers of red fruit and one from white fruit and the lowest, < 0.6% obtained in two numbers of white fruit. Proteomic profile from cutted and blended fresh leaves after extraction using anti proteolytic buffer in coldness, bring us to make a phenogram giving the variability of genetic kinship, that 35 varieties were divided in three groups of kinship; first, all cultivars of red fruit, secondly sixteen cultivars of white fruit, and third one cultivar of white fruit.",